Faciobrachial dystonic seizure can be triggered by swallowing in LGI1 encephalitis - Wendeng Xu; Wei Zhang; Xiaofeng Zhang (BMC Neurology)
Abstract Background Leucine-rich glioma inactivated 1 (LGI1) antibodies are associated with a limbic encephalitis syndrome characterized by faciobrachial dystonic seizures (FBDSs) that is responsive to immunotherapy. The precise pathophysiology, neural origins, and underlying mechanisms of FBDS remain incompletely understood. Case report We present a 54-year-old Chinese female patient with LGI1-related isolated FBDS triggered by swallowing. Discussion FBDS in LGI1-antibody encephalitis exhibit overlapping features with both paroxysmal kinesigenic dyskinesia (PKD) and epileptic motor seizures, both in their clinical manifestations and underlying neural mechanisms. This unique intersection suggests that FBDS represents a pathophysiological borderland between epileptic motor seizures and paroxysmal movement disorders, bridging the gap between these two diagnostic categories. Conclusion FBDS triggered by swallowing expands the clinical spectrum of FBDS and provides new insights into its potential reflex mechanisms, offering a valuable insight for future research into its pathophysiology.